Hungarian Monitoring, 17 March 1988 . [Magyar rádiófigyelő], 1988. március 17 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev's Belgrade visit - Yazov-Carlucci defense ministers' meeting - USSR: reforms in the Party, military role in Afghanistan Domestic Affairs: - 100 million HUF financial assistance for members of Hungarian minorities wishing to settle in Hungary - Kádár holds work talks at Tungsram, makes statement to TV, radio, MTI - Károly Grósz's statement; receives Greek minister of culture - Possibility of alternative military service - Employment policy Economy: - Hungarian National Bank issues bonds worth 150 million DM in the FRG Külpolitika: - Gorbacsov belgrádi látogatása - Jazov-Carlucci honvédelmi miniszteri találkozó - Szovjetunió: reformok a párton belül, afganisztáni katonai szerepvállalás Belpolitika: - 100 millió Ft-os pénzalap a letelepedni szándékozóknak - Kádár munkamegbeszélést tart a Tungsramnál, nyilatkozott a tv-nek, rádiónak, MTI-nek is - Grósz Károly nyilatkozata; fogadja a görög kulturális minisztert - Alternatív katonai szolgálat lehetősége - Foglalkoztatáspolitika Gazdaság: - A MNB 150 millió DM értékben bocsátott ki kötvényt az NSZK-ban